Ellipsis In Arabic Fragment Answers - Algryani, Ali (My University, 2017)
Fragment answers are short answers to questions consisting of non-sentential XPs that convey the same propositional content as complete sentential answers. This squib discusses the syntax of ellipsis in Arabic fragments answers focusing on whether or not ellipsis in fragmentary utterances contains syntactic structure and whether, if so, such fragmentary XPs can be derived via A-bar movement to a clause-initial position plus TP deletion at PF in a way similar to that of Merchant (2004). It is argued that ellipsis in Arabic fragment answers contains syntactic structure and therefore can be analysed as TP ellipsis derived by focus movement of the remnant to a left peripheral position followed by deletion of the TP constituting the background information. Such an analysis captures some morpho-syntactic effects such as morphological case-matching, preposition-stranding, and islands effects.
Keywords: Fragment answers; arabic; Ellipsis